Theoretical analysis of effect of domain inversion shape on second harmonic generation conversion efficiencies of quasi-phase-matched nonlinear optical waveguide devices - Hou, W.X. (2014)
Japanese Journal of Applied Physics, Part 1: Regular Papers and Short Notes and Review Papers